Effectiveness of pneumococcal vaccine in patients with chronic obstructive pulmonary disease (COPD) - Mohanty, Thitta; Patro, Mahismita; Sahoo, Jyotirmaya; Meher, Bijaya Kumar; Pattnaik, Manoranjan; Patra, Jeetendra Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Pneumococcal infections are frequent cause chronic obstructive pulmonary disease (COPD) exacerbations and though various guidelines recommend the use of pneumococcal vaccines routinely to COPD patients to prevent exacerbations, the data regarding the effectiveness of this vaccine is limited and contradictory. Aims and objectives was to compare the frequency of exacerbations in patients of COPD before and after administration of pneumococcal vaccine and to find out the frequency of exacerbations in patients of COPD who are vaccinated against those who are not vaccinated as well as to study the effectiveness of pneumococcal vaccine will be analysed in respect to age, sex, Body mass index (BMI), severity of disease and other co-morbidity. Methods: This was a randomized non-placebo controlled trial, conducted from September 2013 to August 2015 including total of 150 patients divided into two groups: cases and controls. The cases were administered PPV23 along with specific medication and were followed up at intervals of 3months. Exacerbations were identified based on ANTHONISEN’S criteria. Number of exacerbations in each follow-up was recorded. The data from both the groups were analysed statistically. Results: After 1 year of follow up, there was significant reduction in mean number of exacerbations (p value <0.0001) in patients with COPD in vaccinated group. PPV23 was more effective in patients with COPD of less than 65 years of age and with severe and/or very severe airflow obstruction and also in patients with lower BMI (≤21kg/m2), females and with co-morbidities. Conclusions: This is an important strategy to prevent the repeated exacerbations in COPD patients particularly in severe and very severe disease groups and we support the recommendation that pneumococcal vaccine should be administered to these patients.